2002
DOI: 10.1017/s1049023x00010153
|View full text |Cite
|
Sign up to set email alerts
|

Mass Casualty Terrorist Bombings: Comparison of Outcomes by Bombing Type

Abstract: Purpose:To investigate the use of laryngeal mask (LM) in Prehospital Emergency Medicine, to document the experiences with the device, and to develop a staff-training program. Materials: From 01 January 2000 through 31 December 2002, doctors and paramedics placed the LM in victims of respiratory or cardio-respiratory arrests or victims of multiple traumatic injuries. Paramedics were trained in LM placement for a total of 12 hours (video, manikin). Methods: The following information was recorded for each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(90 citation statements)
references
References 0 publications
2
85
0
3
Order By: Relevance
“…About 35,000 cases were attributed to explosions during the war in Iraq and Afghanistan [19]. Meanwhile, the numerous terrorist acts worldwide, especially suicide bomb attacks, have resulted in more than 200,000 explosion-related deaths [20]. Previous studies had confirmed that the mortality of burn-blast combined injury patients was significantly higher than that of burn or blast injury patients.…”
Section: Discussionmentioning
confidence: 99%
“…About 35,000 cases were attributed to explosions during the war in Iraq and Afghanistan [19]. Meanwhile, the numerous terrorist acts worldwide, especially suicide bomb attacks, have resulted in more than 200,000 explosion-related deaths [20]. Previous studies had confirmed that the mortality of burn-blast combined injury patients was significantly higher than that of burn or blast injury patients.…”
Section: Discussionmentioning
confidence: 99%
“…Arnould et al (2004) report median deaths and injuries for six different types of bombings using worldwide data covering 43 events. They are the data entered in the first two rows of columns (1)-(6).…”
Section: Casualtiesmentioning
confidence: 99%
“…Injuries sustained by simulated casualties reflect the most common injuries seen in mass casualty incidents involving blunt trauma injuries. Injury statistics of casualties from railway, aviation, and automotive crashes, fires, and terrorist bombings were reviewed to determine the most common blunt trauma injuries sustained in these disasters [13][14][15][16][17]. The most common blunt trauma injuries found in these disasters were soft tissue injuries, fractures, and head injuries.…”
Section: Experimental Achitecture Designmentioning
confidence: 99%